2019
DOI: 10.1038/s41467-018-08124-7
|View full text |Cite
|
Sign up to set email alerts
|

Strigolactone perception and deactivation by a hydrolase receptor DWARF14

Abstract: The perception mechanism for the strigolactone (SL) class of plant hormones has been a subject of debate because their receptor, DWARF14 (D14), is an α/β-hydrolase that can cleave SLs. Here we show via time-course analyses of SL binding and hydrolysis by Arabidopsis thaliana D14, that the level of uncleaved SL strongly correlates with the induction of the active signaling state. In addition, we show that an AtD14D218A catalytic mutant that lacks enzymatic activity is still able to complement the atd14 mutant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
216
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 216 publications
(233 citation statements)
references
References 34 publications
7
216
1
4
Order By: Relevance
“…MAX2 is an F‐box protein that targets proteins for destruction as part of the ubiquitin–proteasome system (Lechner, Achard, Vansiri, Potuschak, & Genschik, ; Stirnberg, Sande, & Leyser, ). D14 represents a novel system for hormone perception, as this protein both acts as a receptor for strigolactone and degrades strigolactone (Seto et al, ). Binding of strigolactone to D14 facilitates the interaction of D14 with SCF MAX2 (SKP1‐CUL1‐F‐box), an E3 ligase functioning in ubiquitination (Lv et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…MAX2 is an F‐box protein that targets proteins for destruction as part of the ubiquitin–proteasome system (Lechner, Achard, Vansiri, Potuschak, & Genschik, ; Stirnberg, Sande, & Leyser, ). D14 represents a novel system for hormone perception, as this protein both acts as a receptor for strigolactone and degrades strigolactone (Seto et al, ). Binding of strigolactone to D14 facilitates the interaction of D14 with SCF MAX2 (SKP1‐CUL1‐F‐box), an E3 ligase functioning in ubiquitination (Lv et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Targets for MAX2‐directed protein degradation include SUPPRESSOR OF MORE AXILLARY GROWTH2‐LIKE6 (SMXL6), SMXL7, and SMXL8 (Wang et al, ). As D14 also degrades strigolactone, this represents a direct way for terminating the strigolactone signal (Seto et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…) was screened as a potent inhibitor of hydrolysis; it covalently binds to the hydroxyl group of the serine residue in the catalytic domain of D14 . However, Seto et al have shown that intact SL molecules induce an active signaling state in D14 and hydrolysis of SLs is a degradation step . KK094 appears to inhibit SL signaling by occupying the catalytic site of D14 through binding to the serine residue.…”
Section: Inhibitors Of Biosynthesis Perception and Functions Of Strimentioning
confidence: 99%
“…Auch hier half der Verzweigungs-Phänotyp von Mutanten, um Komponenten der Strigolacton-Erkennung und Signalübertragung zu identifizieren. [43,45] Nach Bindung von Strigolacton/D-Ring verändert sich die Konformation von D14 auf eine Weise,dass dieses das F-Box-Protein MAX2/D3 rekrutiert (Abbildung 2). [15] Obwohl es als Rezeptor agiert, behielt D14 seine Hydrolase-Aktivität, und nach der Protein-Ligand-Interaktion wird der Strigolacton-Ligand hydrolysiert (Abbildung 2).…”
Section: Biologische Aktivitäts Ynthetischer Strigolactoneunclassified